Breaking Entry-and Species Barriers: LentiBOOST® Plus Polybrene Enhances Transduction Efficacy of Dendritic Cells and Monocytes by Adenovirus 5 - Strack, Astrid; Deinzer, Anja; Thirion, Christian; Schrödel, Silke; Dörrie, Jan; Sauerer, Tatjana; Steinkasserer, Alexander; Knippertz, Ilka (Viruses, 2022)
Due to their ability to trigger strong immune responses, adenoviruses (HAdVs) in general and the serotype5 (HAdV-5) in particular are amongst the most popular viral vectors in research and clinical application. However, efficient transduction using HAdV-5 is predominantly achieved in coxsackie and adenovirus receptor (CAR)-positive cells. In the present study, we used the transduc-tion enhancer LentiBOOST® comprising the polycationic Polybrene to overcome these limitations. Using LentiBOOST® /Polybrene, we yielded transduction rates higher than 50% in murine bone marrow-derived dendritic cells (BMDCs), while maintaining their cytokine expression profile and their capability to induce T-cell proliferation. In human dendritic cells (DCs), we increased the transduction rate from 22% in immature (i)DCs or 43% in mature (m)DCs to more than 80%, without inducing cytotoxicity. While expression of specific maturation markers was slightly upregulated using LentiBOOST® /Polybrene on iDCs, no effect on mDC phenotype or function was observed. Moreover, we achieved efficient HAdV5 transduction also in human monocytes and were able to subsequently differentiate them into proper iDCs and functional mDCs. In summary, we introduce LentiBOOST® comprising Polybrene as a highly potent adenoviral transduction agent for new in-vitro applications in a set of different immune cells in both mice and humans.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Adenoviral transduction; Adenovirus; Dendritic cells; LentiBOOST®; Monocytes; T cells

CD83 expressed by macrophages is an important immune checkpoint molecule for the resolution of inflammation - Peckert-Maier, Katrin; Langguth, Pia; Strack, Astrid; Stich, Lena; Mühl-Zürbes, Petra; Kuhnt, Christine; Drassner, Christina; Zinser, Elisabeth; Wrage, Marius; Mattner, Jochen; Steinkasserer, Alexander; Royzman, Dmytro; et al. (Frontiers in Immunology, 2023)
Excessive macrophage (M phi) activation results in chronic inflammatory responses or autoimmune diseases. Therefore, identification of novel immune checkpoints on M phi, which contribute to resolution of inflammation, is crucial for the development of new therapeutic agents. Herein, we identify CD83 as a marker for IL-4 stimulated pro-resolving alternatively activated M phi (AAM). Using a conditional KO mouse (cKO), we show that CD83 is important for the phenotype and function of pro-resolving M phi. CD83-deletion in IL-4 stimulated M phi results in decreased levels of inhibitory receptors, such as CD200R and MSR-1, which correlates with a reduced phagocytic capacity. In addition, CD83-deficient M phi upon IL-4 stimulation, show an altered STAT-6 phosphorylation pattern, which is characterized by reduced pSTAT-6 levels and expression of the target gene Gata3. Concomitantly, functional studies in IL-4 stimulated CD83 KO M phi reveal an increased production of pro-inflammatory mediators, such as TNF-alpha, IL-6, CXCL1 and G-CSF. Furthermore, we show that CD83-deficient M phi have enhanced capacities to stimulate the proliferation of allo-reactive T cells, which was accompanied by reduced frequencies of Tregs. In addition, we show that CD83 expressed by M phi is important to limit the inflammatory phase using a full-thickness excision wound healing model, since inflammatory transcripts (e.g. Cxcl1, Il6) were increased, whilst resolving transcripts (e.g. Ym1, Cd200r, Msr-1) were decreased in wounds at day 3 after wound infliction, which reflects the CD83 resolving function on M phi also in vivo. Consequently, this enhanced inflammatory milieu led to an altered tissue reconstitution after wound infliction. Thus, our data provide evidence that CD83 acts as a gatekeeper for the phenotype and function of pro-resolving M phi.
CRIS-Team WoS Importer:2023-03-17

Soluble CD83 modulates human-monocyte-derived macrophages toward alternative phenotype, function, and metabolism. - Peckert-Maier, Katrin; Wild, Andreas; Sprißler, Laura; Fuchs, Maximilian; Beck, Philipp; Auger, Jean-Philippe; Sinner, Pia; Strack, Astrid; Mühl-Zürbes, Petra; Ramadan, Ntilek; Kunz, Meik; Krönke, Gerhard; et al. (Frontiers in Immunology, 2023)
Alterations in macrophage (Mφ) polarization, function, and metabolic signature can foster development of chronic diseases, such as autoimmunity or fibrotic tissue remodeling. Thus, identification of novel therapeutic agents that modulate human Mφ biology is crucial for treatment of such conditions. Herein, we demonstrate that the soluble CD83 (sCD83) protein induces pro-resolving features in human monocyte-derived Mφ biology. We show that sCD83 strikingly increases the expression of inhibitory molecules including ILT-2 (immunoglobulin-like transcript 2), ILT-4, ILT-5, and CD163, whereas activation markers, such as MHC-II and MSR-1, were significantly downregulated. This goes along with a decreased capacity to stimulate alloreactive T cells in mixed lymphocyte reaction (MLR) assays. Bulk RNA sequencing and pathway analyses revealed that sCD83 downregulates pathways associated with pro-inflammatory, classically activated Mφ (CAM) differentiation including HIF-1A, IL-6, and cytokine storm, whereas pathways related to alternative Mφ activation and liver X receptor were significantly induced. By using the LXR pathway antagonist GSK2033, we show that transcription of specific genes (e.g., PPARG, ABCA1, ABCG1, CD36) induced by sCD83 is dependent on LXR activation. In summary, we herein reveal for the first time mechanistic insights into the modulation of human Mφ biology by sCD83, which is a further crucial preclinical study for the establishment of sCD83 as a new therapeutical agent to treat inflammatory conditions.
EVALuna2:549687

Tilting the Balance: Therapeutic Prospects of CD83 as a Checkpoint Molecule Controlling Resolution of Inflammation - Peckert-Maier, Katrin; Royzman, Dmytro; Langguth, Pia; Marosán, Anita; Strack, Astrid; Sadeghi Shermeh, Atefeh; Steinkasserer, Alexander; Zinser, Elisabeth; Wild, Andreas (International Journal of Molecular Sciences, 2022)
Chronic inflammatory diseases and transplant rejection represent major challenges for modern health care. Thus, identification of immune checkpoints that contribute to resolution of inflammation is key to developing novel therapeutic agents for those conditions. In recent years, the CD83 (cluster of differentiation 83) protein has emerged as an interesting potential candidate for such a “pro-resolution” therapy. This molecule occurs in a membrane-bound and a soluble isoform (mCD83 and sCD83, respectively), both of which are involved in resolution of inflammation. Originally described as a maturation marker on dendritic cells (DCs), mCD83 is also expressed by activated B and T cells as well as regulatory T cells (Tregs) and controls turnover of MHC II molecules in the thymus, and thereby positive selection of CD4+ T cells. Additionally, it serves to confine overshooting (auto-)immune responses. Consequently, animals with a conditional deletion of CD83 in DCs or regulatory T cells suffer from impaired resolution of inflammation. Pro-resolving effects of sCD83 became evident in pre-clinical autoimmune and transplantation models, where application of sCD83 reduced disease symptoms and enhanced allograft survival, respectively. Here, we summarize recent advances regarding CD83-mediated resolution of inflammatory responses, its binding partners as well as induced signaling pathways, and emphasize its therapeutic potential for future clinical trials.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Adoptive transfer; CD83; IDO/TGF-β-axis; Pro-resolving macrophages; Resolution of inflammation; Transplantation